The Implementation of the Integrated STEAM Approach to Improve Students' Interest in Science - Almuharomah, Farida Amrul; Sunarno, Widha; Masykuri, Mohammad (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
The study aimed to analyze indigenous scientific knowledge into scientific knowledge through the STEAM approach. Interesting online learning can be done by integrating the local culture of the Plancungan Village. This research uses the Quantitative Descriptive method. Based on research at seven schools in Ponorogo found 83,3% of teachers never used the local culture because teachers know no understands the local culture of the Plancungan village in science material. Respondents were 62 students from Junior High School 1, Junior High School 2, and Junior High School 3. 37,74% of students know this local culture. The value of local culture is contained in the process of making pottery, namely character, aesthetic, historical, and environmental values. STEAM analysis, including science on the process of making pottery, requires a tool in the form of a turntable called